Formation of Religious Moderation Behavior of Students - Siregar, Anwar Fahmi; Rafiq, Mohd. (Fahmina: Jurnal Pendidikan Islam, 2025)
Religious moderation is a balanced, tolerant and non-extreme religious attitude, which is very important to instill in students from an early age. SMP Negeri I Barumun Tengah is one of the schools that runs an independent curriculum in the learning process of Islamic Religious Education. SMP Negeri I Barumun Tengah has students who have different backgrounds, both in terms of economy and religion. But students at SMP Negeri I have an attitude of helping each other and respecting each other. This study aims to analyze how the independent curriculum of Islamic Religious Education contributes to shaping the religious moderation behavior of students at SMP Negeri I Barumun Tengah. The formulation of the problem in this study is how is the process of preparing the Independent Curriculum for Islamic Religious Education at SMP Negeri I Barumun Tengah and what is the content of the values of religious moderation in the Independent Curriculum for Islamic Religious Education at SMP Negeri I Barumun Tengah. This study uses qualitative research methods. Data were collected using observation methods and in-depth interviews with Islamic Religious Education teachers as well as documentation of curriculum tools and learning activities. The results of the study show that the process of preparing the independent curriculum for Islamic Religious Education at SMP Negeri I Barumun Tengah goes through five stages, namely needs analysis, adjustment of learning outcomes, preparation of teaching modules, coordination with school principals and MGMP, as well as implementation and evaluation. The values of religious moderation, namely tolerance, national commitment, anti-violence, accommodating to local culture, tawassuh (taking the middle path), tawazun (continuous), i'hindi (upright and straight), musawah (egalitarian), and shura (deliberation) have been contained in the independent curriculum of Islamic Religious Education at SMP Negeri I Barumun Tengah